Social Structure, Value Orientations and Party Choice in Western Europe - Knutsen, Oddbjørn (Palgrave Studies in European Political Sociology, 2018)
This book analyses the impact of socio-structural variables, such as social class, religion, urban/rural residence, age and gender, on influencing an individual's voting preferences. There have been major changes in recent decades both to social structure and how social structure determines people's voting behaviour. There has also been a shift in value orientations, for example from religious to secular values and from more authoritarian to libertarian values. The author addresses the questions: How do social structure and value orientations influence party choice in advanced industrial democracies?; To what extent is the impact of social structure on party choice transmitted via value orientations?; To what extent is the impact of value orientations on party choice causal effects when controlled for the prior structural variables? The book will be of use to advanced students and scholars in the fields of comparative politics, electoral politics and political sociology. .